The Knowledge of Parents of Children With Diarrhea on Oralit at the Department of Child Health, Dr. Pirngadi General Hospital Medan - Martinus Saragih; Rafita Ramayati; Mansur Karo-Karo; Effendi Harahap; A.H. Sutanto; Helena Siregar (Paediatrica Indonesiana, 1983)
At Dr. Pirngadi General Hospital Medan 285 parents of children with diarrhea had been interviewed about their knowledge on oralit. Only 57.7% of the parents know and use oralit, 12.2.% have known but never used, 13.7.% have only heard while 20.4% never heard of oralit. The main source of information were doctors (63.9%), next come radio and television (7.9%) and then newspaper or magazine (1.8.%). The main supplier or distributor was the dispensary (86.9%).